2015
DOI: 10.1186/s12913-015-1161-0
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in physical access to maternal health services in rural Ethiopia

Abstract: BackgroundIdentifying women with poor access to health services may inform strategies for improving maternal and child health outcomes. The aim of this study was to explore risk factors associated with access to health facilities (in terms of physical distance) among women of reproductive age (15–49 years) in Dabat district, a rural area of north-western Ethiopia.MethodsA randomly selected cross sectional survey of 1,456 rural households was conducted. Data were collected during home visits. Data on household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 23 publications
16
38
0
Order By: Relevance
“…These results slightly differ with what Okwaraji and others found in Ethiopia where educated women lived closer to health centers than uneducated women (Adjusted mean difference travel time -41 min 95% CI -50;-31). Women aged 15-20 years were more likely to live in poor access areas compared with women aged 21-30 years (adjusted mean difference travel -11 min 95% CI -23-0) [3]. One would expect the association between maternal age and complications to be significant since there is biological plausibility to that effect.…”
Section: Sociodemographic Findings and Maternal Health Outcomesmentioning
confidence: 96%
See 1 more Smart Citation
“…These results slightly differ with what Okwaraji and others found in Ethiopia where educated women lived closer to health centers than uneducated women (Adjusted mean difference travel time -41 min 95% CI -50;-31). Women aged 15-20 years were more likely to live in poor access areas compared with women aged 21-30 years (adjusted mean difference travel -11 min 95% CI -23-0) [3]. One would expect the association between maternal age and complications to be significant since there is biological plausibility to that effect.…”
Section: Sociodemographic Findings and Maternal Health Outcomesmentioning
confidence: 96%
“…High maternal education and early care seeking, utilization of orthodox health facilities and drug use at home age <1 year were associated with early care seeking outside home and utilization of orthodox health services (p<0.001) [3]. Logistic regression showed that high maternal education and high family socio-economic status were strong predictors of early care seeking and care seeking outside home, maternal age, maternal education and family socio-economic status are predictors of appropriate health care-seeking behaviors for children [3].…”
Section: Introductionmentioning
confidence: 97%
“…Access to comprehensive, quality health care services is important for promoting and maintaining health, preventing and managing the disease, reducing unnecessary disability and premature death, and achieving health equity for all women [7][8][9][10]. It agreed that socio-demographic, cultural, and geographical and literacy level and economic conditions plays a vital role to affect the accessibility and utilization of health care services among women [11][12][13][14][15]. Reproductive, maternal, newborn and child health are indictors of equity in health care access in the country [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that literacy levels, economic conditions, socio-demographic and cultural characteristics, and geographical disparities play a vital role in affecting the accessibility and utilization of health care services among women [16][17][18][19][20]. Troubles conditions in accessing health care among reproductive-age women lead to diverse adverse health outcomes like unwanted pregnancies, unsafe abortion, maternal and child mortality resulting from low family planning uptakes, and home deliveries [7,9,14,15,21].…”
Section: Introductionmentioning
confidence: 99%